The heterogeneity of negative problem orientation in Chinese adolescents: A latent profile analysis - Lin, Rong-Mao; Xiong, Xia-Xin; Shen, Yi-Lin; Lin, Nan; Chen, Yan-Ping (Frontiers in Psychology, 2022)
Negative problem orientation (NPO) has become an essential construct for comprehending social problem-solving deficits. However, the heterogeneity of NPO has not yet been explored. With a sample of Chinese adolescents (N = 2,174), four latent profiles were identified as lower NPO, moderate NPO, self-inefficacy and negative outcome expectancy (SI&NOE), and dysfunctional NPO. Compared to the lower NPO and moderate NPO, a greater percentage of boys in the SI&NOE and dysfunctional NPO profiles than were girls. In addition, lower grades and younger adolescents tended to engage in the moderate NPO and SI&NOE profiles. The dysfunctional NPO reported higher levels of worry, depressive symptoms, anxiety, and stress, and worse sleep quality than the other profiles. The implications of these findings are discussed herein.